Association of peripheral monocytic myeloid-derived suppressor cells with molecular subtypes in single-center endometrial cancer patients receiving carboplatin + paclitaxel/avelumab (MITO-END3 trial) - C. D’Alterio; G. Rea; M. Napolitano; E. Coppola; A. Spina; D. Russo; R. Azzaro; C. Mignogna; G. Scognamiglio; D. Califano; L. Arenare; C. Schettino; et al. (Cancer Immunology, Immunotherapy)
Abstract The MITO-END3 trial compared carboplatin and paclitaxel (CP) with avelumab plus carboplatin and paclitaxel (CPA) as first-line treatment in endometrial cancer (EC) patients and demonstrated a significant interaction between avelumab response and mismatch repair status. To investigate prognostic/predictive biomarker, 29 MITO-END3-EC patients were evaluated at pretreatment (B1) and at the end of CP/CPA treatment (B2) for peripheral myeloid-derived suppressor cells (MDSC) and Tregs. At B2, effector Tregs frequency was significantly higher in patients treated with CPA as compared to CP (p = 0.038). Both treatments (CP/CPA) induced significant decrease in peripheral M-MDSC (− 5.41%) in TCGA 2-MSI-high as compared to TCGA-category 4 tumors (p = 0.004). In accordance, both treatments induced M-MDSCs (+ 5.34%) in MSS patients as compared to MSI-high patients (p = 0.001). Moreover, in a subgroup of patients, primary tumors were highly infiltrated by M-MDSCs in MSS as compared to MSI-high ECs. A post hoc analysis displayed higher frequency of M-MDSCs (p = 0.020) and lower frequency of CD4+ (p < 0.005) at pretreatment in EC patients as compared to healthy donors. In conclusion, the peripheral evaluation of MDSCs and Tregs correlated with molecular features in EC treated with CP/CPA and may add insights in identifying EC patients responder to first-line chemo/chemo-immunotherapy. Graphical abstract